The Gesus Hedyotis Linn. in Maharastra State - Rao, Rolla S.; Hemadri, K. (Indian Forester, 1973)
The genus Hedyotis L. as understood at present and as interpreted in the modern floras is presented in this paper with tbe relevaut synonymy, two new combinations as necessary and distribution based on collections from various districts out of the 26 districts of the Maharastra state. Incidentally 10 new combinations of Western Peninsular India species which are not 10 far recorded within the Maharastra State but studied now, are also added in this paper.